Working capital management and firm profitability: evidence from emerging markets. (17th June 2019) - Orazalin, Nurlan
The purpose of this study is to provide empirical evidence on the relationship between working capital management (WCM) and the profitability of top manufacturing firms in two main emerging markets in the Commonwealth Independent States (CIS) region. The study employs panel data methodology using data of top manufacturing firms operating in Kazakhstan and Russia over the period 2010-2014. The empirical results show that Kazakh firms, following more aggressive strategies of working capital, exhibit higher profitability than Russian firms. The study also established a linear relationship between profitability and working capital, which indicates the absence of an optimal working capital level that could maximise the profitability of Kazakh and Russian firms. The findings indicate that managers can maximise shareholder value by following more aggressive practises of WCM in transition economies similar to Kazakhstan and Russia.